Our team: PhD Student Latifa Mrisho - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2017)
Our team: PhD Student Latifa Mrisho shares on her research at IITA in Tanzania on whiteflies - the major vector driving the dual cassava viral diseases pandemic in Eastern, Central and parts of Southern Africa.